EVALUASI PURNA HUNI STADION SULTAN AGUNG BANTUL MANAJEMEN PEMELIHARAAN BANGUNAN - Arifin, Syaiful; Mulyandari, Hestin (Jurnal Arsitektur dan Perencanaan (JUARA), 2019)
Sultan Agung Bantul Stadium is a sport area in Bantul Regency, but it is rather poorly maintained. The Post Occupancy Evaluation (POE) aims to know about problems that cause the poor condition of the building to support sports activities. The method uses a descriptive research in the form of evaluation of habitation. This method is an explanation of the data that has been collected that is supported and applied to existing theories. The collection of data with a survey on the environment Sultan Agung Stadium and collecting data from the government as a guide in designing. However, an analysis of the Building Maintenance Management of this stadium is also needed. In the design department Sultan Agung Stadium in Bantul district has a lot of potential that can be developed as a sport.